2009
DOI: 10.1159/000239753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rinsing with Mouthwashes after Brushing with a Fluoridated Toothpaste on Salivary Fluoride Concentration

Abstract: The aim of the study was to determine whether rinsing with a mouthwash after brushing with a fluoridated toothpaste affected oral fluoride (F) retention and clearance compared with an oral hygiene regime without mouthwash. In this supervised, single-blind study, 3 regimes were compared: (A) brushing for 1 min with 1 g of 1,450 μg F/g NaF toothpaste followed by rinsing for 5 s with 10 ml water; (B) as A but followed by rinsing for 30 s with 20 ml of 100 mg F/l NaF mouthwash, and (C) as B but rinsing for 30 s wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…There were, however, large SD values, which is in accordance with other studies [16,25]. This variation could be due to individual behaviour factors, for example the amount of toothpaste used, amount of rinsing water, number of rinsing sessions or motor activity by the lips, tongue and cheeks.…”
Section: Discussionsupporting
confidence: 91%
“…There were, however, large SD values, which is in accordance with other studies [16,25]. This variation could be due to individual behaviour factors, for example the amount of toothpaste used, amount of rinsing water, number of rinsing sessions or motor activity by the lips, tongue and cheeks.…”
Section: Discussionsupporting
confidence: 91%
“…The F concentration of each expectorated saliva/toothpaste sample as well as each toothpaste collected was also measured directly using a F-ISE, based on the procedure of Duckworth et al 20 . Food samples were analysed for F concentration after overnight hexamethyldisiloxane-facilitated diffusion using a F-ISE.…”
Section: Methodsmentioning
confidence: 99%
“…The use of a fluoride mouthrinse at concentrations of 0.05% NaF or above after brushing with fluoride toothpaste may also be advantageous for individuals who normally rinse with water after brushing, based on oral fluoride retention studies (Zero et al, 1988;Duckworth et al, 2009;Mystikos et al, 2011). Assisted/Supervised Rinsing up to Age 8 yrs -Parent/ caregiver should control the amount of mouthrinse dispensed and the length of the rinsing time A Cochrane review (Marinho et al, 2003c) has shown that supervising a child's use of self-administered fluoride (toothpaste or mouthrinse) leads to greater benefits.…”
Section: Rinsing Time -Ideally 1 Minutementioning
confidence: 99%